Regional economic integration in Europe: Effects and open issues - Petrović Pero; Antevski Miroslav (Međunarodni Problemi)
In analyzing regional economic integration in Europe the authors pay special attention to the development in the European Union, for other forms of regional or sub regional integration at the continent are in fact mostly transitional and provisional, and directly connected with EU. The authors argue that in spite of considerable success and high level of integration of the EU, several important open issues remain in that process. They are results of mixed character of European integration: political and economic. Too many kinds of interests are of opposed character, and it is very hard to harmonize them in real politics. The main problems in the EU have their cause in the nature of European integration: international competitiveness of European economy, social character of European states, national productivity, challenges of enlargement.